(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Abnormal uterine bleeding (AUB) is the most common reason for gynecological visits for perimenopausal bleeding and may account for more than 25% of all hysterectomies. Objective: This study was aimed to review the causes of abnormal uterine bleeding in perimenopausal women establishing the correlation with ultrasonographic and histopathological examinations. Study Method: This descriptive study was conducted in the department of gynecology and obstetrics, Ibn Sina Medical College, Dhaka during January to December 2012. Two hundred and eleven women were selected for this study, who admitted into the hospital with abnormal uterine bleeding in perimenopausal age. The clinical, ultrasonographic and histopathological findings of these women were evaluated in this study. Results: Menorrhagia was the major symptom (52.6%) irrespective of age and parity. All these women underwent D&C followed by either medical management or hysterectomy depending upon the diagnosis. The histopathological findings of endometrium were analyzed and confirmed as fibroid uterus (58.28%) and DUB (17.58%) correlated well with transvaginal sonography (TVS) and histopathological examination. Hysterectomy conferred other uterine lesions as adenomyosis (18.71%), endometrial polyp (4.81%) and malignancy (1.06%). Conclusion: Abnormal uterine bleeding in perimenopausal age group is a common but ill-defined entity which needs proper evaluation. Accurate diagnosis of the causative factors of AUB in this age group is of utmost importance so that appropriate management can be established early that leads the minimization of the patients sufferings. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18295 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.135-139